Superhydrophobic surfaces as a tool for the fabrication of hierarchical spherical polymeric carriers - Costa, A. M. S. (2015)
Hierarchical polymeric carriers with high encapsulation efficiencies are fabricated via a biocompatible strategy developed using superhydrophobic (SH) surfaces. The carries are obtained by the incorporation of cell/BSA-loaded dextran-methacrylate (DEXT-MA) microparticles into alginate (ALG) macroscopic beads. Engineered devices like these are expected to boost the development of innovative and customizable systems for biomedical and biotechnological purposes.